Platelet and Leukocyte Count Difference on Clinical Degrees of Dengue in Children in Dr Moewardi Hospital Surakarta. - Putro, Jati Febriyanto Adi Listyono; Nugroho, Hari Wahyu; ., Hudiyono (Nexus Kedokteran Klinik, 2015)
Background: Dengue Hemmorhagic Fever is still one of the major public health problem in Indonesia. The classification of Dengue severity from mild to severe is very important because it can prevent the progression of Dengue. Unfortunately the WHO 2011 criteria for Dengue severity only contains the clinical symptoms of patients without including the exact value of complete blood count, like platelet and leukocyte, in each degree. This study was conducted to determine whether there was a difference between the value of platelet and leukocyte in each clinical degree of Dengue Methods: This research was an analytical observational study with cross sectional approach. It was carried out in Dr. Moewardi hospital, Surakarta from July to October 2014. Children who were hospitalized in Dr. Moewardi hospital from January 1st to December 31st 2013 whom fulfill all of the inclusion criteria and none of the exclusion criteria were eliglible. Data was taken from medical record an analyzed using Kruskal-Wallis test and Spearman test. Results: Among 203 patiens were diagnosed with Dengue hemorrhagic fever, 113 (55%) patients were in DHF 1, 52 (25%) patiens were in DHF 2, and 38 (20%) were DSS patients. The difference of platelet count in each degree was significant (p=0,01). The difference of leukocyte in each degree was significant (p=0,002). The association between platelet count and clinical Dengue degree was statistically significant (p=0,005) with very weak negative correlation (r=-0,198). The association between leukocyte count and clinical Dengue degree was statistically significant (p=0,001) with weak positive correlation (r=0,227) Conclusions:There are significant differences of platelet and leukocyte count in clinical Dengue degree of children in Dr. Moewardi hospital, Surakarta. There are no correlation between platelet and leukocyte with clinical Dengue degree of children in Dr. Moewardi hospital, Surakarta although statistically significant. Keywords: Dengue hemorrhagic fever, platelets, lekocytesÂ